1984
DOI: 10.1159/000120159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temporary Subdural-Peritoneal Shunt on Subdural Effusion with Subarachnoid Effusion

Abstract: A special entity called subdural effusion with ruptured subarachnoid effusion, which was diagnosed by CT, air study, and RI cisteraography, was observed in 14 children of up to 10 months of age. 10 cases that showed symptoms of increased intracranial pressure (ICP) were treated by temporary subdural-peritoneal (S-P) shunt, and the remaining 4 cases that showed no symptoms of increased ICP were treated conservatively. 9 of the 10 cases treated by S-P shunt and 2 of the 4 cases treated conservatively showed good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…Compression by the subdural mass and constricting of the brain by membranes may be the causing factors as Rabe et al [11] had described. No correlation existed in our cases between these CT find ings and the clinical outcome in accordance with reports from other authors [5,15]. The clinical outcome was more dependent of the under lying disease, e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Compression by the subdural mass and constricting of the brain by membranes may be the causing factors as Rabe et al [11] had described. No correlation existed in our cases between these CT find ings and the clinical outcome in accordance with reports from other authors [5,15]. The clinical outcome was more dependent of the under lying disease, e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Although removal of the SP shunts after resolution of the subdural fluid collection has been advocated or achieved by some others [1,5,13,14,21,24], Litofsky et al [11] did not observe an adverse effect in 37 patients who had not had their shunts removed. The interval between the shunt insertion and removal ranged from 4 to 12 weeks in studies reported in the literature [1,5,14].…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment modalities have been used in the management of infantile chronic subdural fluid collections, such as subdural taps [1,12], evacuation of the hematoma and excision of the membranes by a wide craniotomy [9], internal drainage of the subdural fluid into a body cavity such as the pleura or the peritoneum [4,5,20], subgaleal shunt [18] and subdural drainage [7,8]. Although subduroperitoneal (SP) shunts have been widely used in the management of subdural fluid collections [3,5,7,8,11,13,14,24], publications on their complications are few in number. In this study, we retrospectively reviewed the complications of SP shunting performed in our institution.…”
Section: Introductionmentioning
confidence: 99%
“…Subdural taps may also result in subdural effusion due to traumatic subarachnoid rupture. For patients whose course is complicated by an expanding or symptomatic subdural fluid collection, we usually make burr holes and irrigate, but if the clinical symptoms do not improve and the fluid collection does not decrease in size, we insert a unilateral subdural-peritoneal shunt [4,21,39]. The shunt does not necessarily need to be removed after resolution of the fluid collection.…”
Section: A N a G E M E N Tmentioning
confidence: 99%